Persistent effects of swine manure biochar and biogas slurry application on soil nitrogen content and quality of lotus root - Zhang, Mengyu; Cui, Jiatao; Mi, Meng; Jin, Zewen; Wong, Ming Hung; Shan, Shengdao; Ping, Lifeng (Frontiers in Plant Science, 2024)
Using swine manure biochar and biogas slurry in agriculture proves to be an effective strategy for soil improvement and fertilization. This approach reduces the dependency on chemical fertilizer and enhances the efficiency and resource utilization of livestock waste. In this study, a pot trial on the growth of lotus root was conducted to investigate the persistent effects of applying 350°C swine manure biochar (1% and 2%) and biogas slurry (50% and 100%) on soil nitrogen nutrient and lotus root quality. The results showed that compared to chemical fertilizer alone (A0B0), swine manure biochar significantly increased soil nitrogen content after one year of application. The contents of total nitrogen (TN), alkali-hydrolyzed nitrogen (AHN), ammonium nitrogen (NH4+-N), and nitrate nitrogen (NO3--N) increased by 17.96% to 20.73%, 14.05% to 64.71%, 17.76% to 48.68% and 2.22% to 8.47%, respectively, during the rooting period. When swine manure biochar was present, the application of biogas slurry further elevated soil nitrogen content. The co-application of swine manure biochar and biogas slurry significantly increased soil nitrogen content, and the 100% nitrogen replacement with biogas slurry combined with 2% swine manure biochar (A2B2) treatment exhibited the most significant enhancement effect during whole plant growth periods. Soil enzyme activities, including soil protease (NPT), leucine aminopeptidase (LAP), β-glucosidase (β-GC) and dehydrogenase (DHA), showed a tendency to increase and then decrease with the prolongation of lotus root fertility period, reaching the maximum value during the rooting period. Compared to A0B0, the treatment with 2% swine manure biochar had the most significant effect on enzyme activities and increased the lotus root's protein, soluble sugar, and starch contents. Nitrate content decreased with the application of 2% swine manure biochar as the amount of biogas slurry increased. In conclusion, swine manure biochar effectively improved soil nitrogen content, enzyme activity, and lotus root quality. Even after one year of application, 2% swine manure biochar had the best enhancement effect.